Bio-based flame-retardant flexible polyurethane foam with photo-thermal conversion performance as well as preparation method and application of bio-based flame-retardant flexible polyurethane foam
By using bio-based materials and flame-retardant polyols and other components, bio-based polyurethane soft bubbles with photothermal conversion and flame-retardant properties are prepared, which solves the problems of low efficiency and high flammability in oil-water separation and flame-retardant separation, and achieves rapid treatment and efficient flame-retardant effects on high-viscosity crude oil.
Patent Information
- Application Number
- CN202411787151.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-06
AI Technical Summary
Existing polyurethane foams have problems of low efficiency and high flammability in oil-water separation and flame retardant, especially in dealing with high viscosity crude oil pollution and fire safety.
Bio-based flame-retardant polyurethane soft bubbles with photothermal conversion properties are prepared by specific process steps using bio-based materials such as vanilla alcohol and castor oil, combined with flame-retardant polyol and MXene powder. The material improves its mechanical properties, superhydrophobicity and flame retardant properties by curing with loading Ti3C2Tx and PDMS.
It achieves rapid heating and adsorption of high-viscosity crude oil, has excellent oil-water separation performance and good flame retardant properties, and the ultimate oxygen index can reach 27.3%, which significantly improves the safety and environmental friendliness of the material.
Smart Images

Figure CN119570108A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of bio-based polyurethane foam, and specifically relates to a bio-based flame-retardant polyurethane soft foam with light-to-heat conversion performance, and a preparation method and application thereof. Technical Background
[0002] As the fifth largest synthetic polymer material, polyurethane (PU) plays a very important role in life and industry due to its good mechanical properties, thermal insulation and chemical resistance. Polyurethane foam is widely used in the construction, automotive and electronics industries, which require materials to have excellent performance in various aspects, such as oil-water separation, electromagnetic shielding, thermal insulation / fire protection, etc.
[0003] At present, the raw materials for the production of commercial polyurethane foams used for oil-water separation mainly come from limited petrochemical resources, and the foams are usually directly discarded or incinerated after use, which will cause secondary pollution to the environment. Therefore, it is very necessary to find biomass resources to partially replace petrochemical resources to prepare environmentally friendly polyurethane soft foam oil-absorbing materials. Compared with commonly used petroleum-based polyols, vegetable oils have the advantages of abundant raw material sources, low energy consumption, and good physical and chemical stability. Traditional polyurethane soft foam oil-absorbing materials are mainly used to treat light oil pollution, while the cleaning of high-viscosity oil pollution has the problems of slow adsorption efficiency and low oil-water separation efficiency. With the increase in human demand for crude oil extraction, crude oil leakage accidents occur frequently. How to quickly deal with crude oil pollution with high viscosity and low fluidity has become an urgent problem to be solved. Crude oil is temperature sensitive, and its viscosity decreases with increasing temperature. Therefore, the development of polyurethane foams with photothermal conversion properties will be conducive to the rapid heating and adsorption of high-viscosity crude oil.
[0004] When using polyurethane foam to treat oil pollution, fire safety requirements are very high. However, due to the porous structure of polyurethane foam, oxygen can easily diffuse into the foam, which accelerates the ignition process. Therefore, polyurethane foam is highly flammable, which increases the risk of fire and poses a major threat to personnel and property safety during use. Therefore, it is urgent to develop environmentally friendly polyurethane flame retardant foam. At present, the research on polyurethane flame retardancy is mainly divided into additive and reactive flame retardant. Additive flame retardant is to add flame retardant substances to the polyurethane system in the form of fillers, mainly including inorganic, organic and composite flame retardants, etc., with simple process and low cost, but the flame retardant effect is not long-lasting; reactive flame retardants mainly achieve flame retardancy through flame retardant elements such as phosphorus, nitrogen, silicon and their own flame retardant chemical structure. Unlike additive flame retardants, reactive flame retardants can be connected to the polyurethane substrate by chemical bonding, so as to be well compatible with the polyurethane matrix. While achieving the flame retardant effect, the special structure of some reactive flame retardants can also improve the mechanical properties and thermal properties of polyurethane. Summary of the invention
[0005] Technical problem to be solved: In view of the shortcomings of existing oil-water separation and flame-retardant material preparation technologies, the present invention provides a bio-based flame-retardant polyurethane soft foam with photothermal conversion performance and a preparation method and application thereof. The polyurethane soft foam can be used for oil-water separation and has good photothermal conversion and flame-retardant properties.
[0006] Technical solution: A method for preparing a bio-based flame-retardant polyurethane soft foam with photothermal conversion performance, comprising the following steps:
[0007] (1) Vanillyl alcohol is dissolved in a NaOH aqueous solution to obtain a brown-yellow sodium phenolate aqueous solution, and then phenylphosphoryl dichloride is dissolved in ethyl acetate and added dropwise to the sodium phenolate aqueous solution under ice bath conditions, wherein the molar ratio of vanillyl alcohol to phenylphosphoryl dichloride is 1.8-2.5:1, to obtain an upper pale yellow liquid, which is washed with a NaOH aqueous solution and hot water, respectively, and rotary evaporated to obtain a yellow viscous liquid, i.e., a flame retardant polyol; (2) By weight, 40-80 parts of castor oil, 0-20 parts of flame retardant polyol, 20 parts of polytetrahydrofuran, 5-10 parts of MXene powder, 2.0-3.6 parts of foaming agent, 1.0-2.0 parts of catalyst, and 1.2-2.4 parts of foam stabilizer are mixed uniformly to prepare component A; 55-65 parts of isocyanate of component B are added to component A, and after foaming and aging, a loaded Ti3C2T x Polyurethane soft foam; (3) Loading Ti3C2T x The polyurethane soft foam is immersed in 1wt.% to 5wt.% PDMS n-hexane solution and ultrasonically treated, and then dried and solidified to obtain a bio-based flame-retardant polyurethane soft foam with photothermal conversion performance.
[0008] Preferably, in step (1), the molar ratio of vanillyl alcohol to phenylphosphoryl dichloride is 2.2:1, and the concentration of the NaOH aqueous solution is 2.2 mol·L -1 .
[0009] Preferably, the hydroxyl value of the flame retardant polyol in step (1) is 60 to 65 mg KOH·g -1 .
[0010] Preferably, the weight proportions of the components in step (2) are as follows: 40-80 parts of castor oil, 20 parts of flame retardant polyol, 20 parts of polytetrahydrofuran, 8 parts of MXene powder, 3.0 parts of foaming agent, 1.3 parts of catalyst, 1.8 parts of foam stabilizer, and 55-65 parts of isocyanate.
[0011] Preferably, in step (2), the catalyst is at least one of triethylenediamine, N-methylmorpholine, N-ethylmorpholine and stannous octoate; the foam stabilizer is one of Maitu L580 and Maitu L-3881; and the isocyanate is any one of toluene diisocyanate, diphenylmethane diisocyanate, polyphenylmethane polyisocyanate and isophorone diisocyanate.
[0012] Preferably, the MXene powder in step (2) is a single layer Ti3C2T x powder.
[0013] Preferably, in step (2), castor oil, polytetrahydrofuran, and MXene powder are first stirred and ultrasonically dispersed for 1 to 2 hours to be fully mixed, and then mixed with flame retardant polyol, foaming agent, catalyst, and foam stabilizer at 600 r·min. -1 Stir for 3 to 6 minutes to mix evenly.
[0014] Preferably, the temperature in the aging step in step (2) is 50-100° C. and the time is 10-36 hours; the ultrasonic treatment time in step (3) is 0-2 hours, the curing temperature is 60-100° C. and the curing time is 10-24 hours.
[0015] The bio-based flame-retardant polyurethane soft foam with light-to-heat conversion performance prepared by the above method.
[0016] The above-mentioned bio-based flame-retardant polyurethane soft foam is used in oil-water separation and flame retardancy.
[0017] Beneficial effects: (1) In the present invention, vanillin alcohol and castor oil derived from biomass resources are used to replace part of the petrochemical-based polyether polyols, and the prepared polyurethane soft foam is green and environmentally friendly;
[0018] (2) The bio-based polyurethane soft foam prepared in the present invention has super hydrophobicity and lipophilicity, and the water contact angle can reach 154.6°, which can effectively realize the continuous adsorption and separation of oil-water mixture;
[0019] (3) The castor oil-based polyurethane soft foam prepared in the present invention has good photothermal conversion performance and flame retardant properties. It can quickly heat up to 95.3°C under 1 sun illumination, and its saturated adsorption capacity for crude oil can reach 4.92 g·g -1 , the limiting oxygen index can reach a flame retardant effect of about 27%. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the H-NMR spectrum of the vanillyl alcohol-based flame retardant polyol prepared in Example 2.
[0021] Figure 2 This is the SEM image of the composite foam material prepared in Example 6.
[0022] Figure 3 The compressive stress-strain curves of the foam materials prepared in Examples 3 and 6 under 70% strain conditions are shown in FIG.
[0023] Figure 4 This is a thermogravimetric comparison diagram of the composite foam materials prepared in Examples 3 to 6.
[0024] Figure 5 This is the absorption capacity of the composite foam material prepared in Example 6 for various organic liquids and oils.
[0025] Figure 6 This is a schematic diagram of the crude oil adsorption process of the composite foam material prepared in Example 6 with and without light conditions.
[0026] Figure 7 This is a photothermal conversion diagram of the composite foam materials prepared in Example 3 and Example 6. DETAILED DESCRIPTION
[0027] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the spirit and essence of the present invention, modifications and substitutions made to the method, steps or conditions of the present invention all belong to the scope of the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art.
[0028] Example 1
[0029] Step 1: Add 1.8 g LiF to 40 mL 9 M hydrochloric acid solution and stir for 10 min (500 r / min) in an ice bath. -1 ) to obtain a uniform etching solution; add 1.9 g MAX (Ti3AlC2, 400 mesh, purchased from Foshan Xinxi Technology Co., Ltd.), and stir the reaction at 35°C for 24 hours, and the time can be appropriately extended to obtain a multilayer MXene solution;
[0030] Step 2: The obtained solution was heated at 4000 r / min -1 Centrifuge for 5 min, wash repeatedly with deionized water 5-6 times, and ultrasonicate for 1 h; repeat centrifugation and add water to repeatedly peel off the lower sediment until dark green Ti3C2T x Suspension, collect the prepared single-layer MXene solution;
[0031] Step 3: The collected single-layer MXene solution was freeze-dried for 48 h and ground to obtain MXene powder.
[0032] Example 2
[0033] Step 1: Dissolve 0.22 mol of vanillyl alcohol (33.9 g) in 100 mL of NaOH (8.8 g, 0.22 mol) aqueous solution and stir at room temperature for 10 min to generate a brown-yellow aqueous solution of sodium phenolate;
[0034] Step 2: Dissolve 0.1 mol of phenylphosphoryl dichloride (19.5 g) in 200 mL of ethyl acetate, add dropwise to the aqueous solution of sodium phenolate in an ice bath over 3 h, stir, and continue to react at room temperature for 1 h after the addition is completed, and let stand to obtain a pale yellow liquid on the upper layer;
[0035] Step 3: Washing with 4 wt % NaOH aqueous solution twice and hot water three times, and then rotary evaporating to obtain a yellow viscous liquid, namely, flame retardant polyol.
[0036] Example 3
[0037] Step 1: Mix 80 parts of castor oil and 20 parts of polytetrahydrofuran in proportion, add 3.0 parts of deionized water as a foaming agent, 0.6 parts of triethylenediamine, 0.7 parts of stannous octoate and 1.8 parts of foam stabilizer Momentive L580, and stir at 600 r / min. -1 The precursor solution of component A was prepared by stirring for 5 minutes to mix well. 62.5 parts of diphenylmethane diisocyanate were added to the precursor solution and the mixture was stirred at 1200 r·min. -1 The mixture was stirred at a speed of 10 s, foamed naturally, and aged at 60°C for 24 h to obtain polyurethane soft foam.
[0038] Example 4
[0039] Step 1: By weight, 60 parts of castor oil, 20 parts of polytetrahydrofuran and 20 parts of hydroxyl value 62.5 mg KOH g -1 The flame retardant polyols were mixed in proportion, 3.0 parts of deionized water as a foaming agent, 0.6 parts of triethylenediamine, 0.7 parts of stannous octoate and 1.8 parts of foam stabilizer Momentive L580 were added, and the mixture was stirred at 600 r / min. -1 The precursor solution of component A was prepared by stirring for 5 minutes to mix well. 58.4 parts of diphenylmethane diisocyanate were added thereto and the mixture was stirred at 1200 r·min. -1 The mixture was stirred at a speed of 10 s, foamed naturally, and aged at 60°C for 24 h to obtain a flame retardant polyurethane soft foam.
[0040] Example 5
[0041] Step 1: According to weight, 60 parts of castor oil, 20 parts of polytetrahydrofuran and 8 parts of MXene powder were heated at 400 r·min. -1 After stirring for 30 min, ultrasonic dispersion was performed for 1 h to fully mix the mixture. Then, 20 parts of KOH (hydroxyl value: 62.5 mg g) was added. -1The flame retardant polyol was mixed with 3.0 parts of deionized water as a foaming agent, 0.6 parts of triethylenediamine, 0.7 parts of stannous octoate and 1.8 parts of foam stabilizer Momentive L580 at 600 r / min. -1 The precursor solution of component A was prepared by stirring for 5 minutes to mix well. 58.4 parts of diphenylmethane diisocyanate were added thereto and the mixture was stirred at 1200 r·min. -1 The mixture was stirred at a speed of 10 s, foamed naturally, and aged at 60 °C for 24 h to obtain the loaded Ti3C2T x Flame retardant polyurethane soft foam.
[0042] Example 6
[0043] Step 1: According to weight, 60 parts of castor oil, 20 parts of polytetrahydrofuran and 8 parts of MXene powder were heated at 400 r·min. -1 After stirring for 30 min, ultrasonic dispersion was performed for 1 h to fully mix the mixture. Then, 20 parts of KOH (hydroxyl value: 62.5 mg g) was added. -1 The flame retardant polyol was mixed with 3.0 parts of deionized water as a foaming agent, 0.6 parts of triethylenediamine, 0.7 parts of stannous octoate and 1.8 parts of foam stabilizer Momentive L580 at 600 r / min. -1 The precursor solution of component A was prepared by stirring for 5 minutes to mix well. 58.4 parts of diphenylmethane diisocyanate were added thereto and the mixture was stirred at 1200 r·min. -1 The mixture was stirred at a speed of 10 s, foamed naturally, and aged at 60 °C for 24 h to obtain the loaded Ti3C2T x Flame retardant polyurethane soft foam;
[0044] Step 2: PDMS and curing agent were mixed in a mass ratio of 10:1 and dissolved in n-hexane to prepare a 1wt.% PDMS n-hexane solution; Ti3C2T x The flame-retardant polyurethane soft foam was immersed in 1 wt % PDMS n-hexane solution and ultrasonically treated for 1 h, and then cured in an oven at 80° C. for 12 h to obtain a multifunctional castor oil-based polyurethane soft foam.
[0045] Table 1 Comparison of properties of multifunctional castor oil-based polyurethane soft foam prepared in various embodiments
[0046]
[0047] As can be seen from Table 1, the water contact angle of the multifunctional castor oil-based polyurethane soft foam prepared by the present invention is 95.9° to 154.6°, the compressive stress is 0.046 to 0.848 MPa, and the flame retardant performance is represented by the limiting oxygen index (LOI), which can reach 16.3 to 27.3%. Among them, Example 6 has the best comprehensive performance, with a contact angle of 154.6°. Under the condition of 70% strain, the mechanical property test is carried out, the compressive stress can reach 0.848 MPa, and the flame retardant limiting oxygen index can reach 27.3%.
[0048] The flame retardant polyol PPDVA prepared in Example 2 was 1 H NMR spectrum analysis, the results are as follows Figure 1 As shown, the corresponding relationship between each proton and the proton peak has been marked. The peak at 8.07-7.43 ppm represents the hydrogen in the benzene ring directly connected to the phosphorus atom. The peaks at 7.15-6.69 ppm, 4.51 ppm and 3.65 ppm represent the benzene ring, methylene and methoxy structures consistent with the vanillyl alcohol group, respectively.
[0049] The polyurethane composite foam prepared in Example 3 was characterized by SEM morphology. Figure 2 As shown, the uniform rough structure on the foam surface indicates that Ti3C2T x The inset shows the contact angle (WCA) of the composite foam, which reaches 154.6°, indicating that the foam has excellent superhydrophobicity.
[0050] The mechanical properties of the polyurethane foams prepared in Example 3 and Example 6 were analyzed. Figure 3 As shown, under 70% strain conditions, the compressive stress of Example 6 is significantly improved compared with Example 3 (0.112 MPa), reaching 0.848 MPa, which has excellent mechanical properties and improves the recyclability of the polyurethane soft foam.
[0051] The thermal properties of the polyurethane foams prepared in Examples 3-6 were analyzed. The thermogravimetric results are as follows: Figure 4 As shown in the figure, the residual carbon rate of Example 6 in nitrogen at 800°C is as high as 16.52%, which is 12.38% higher than the residual carbon rate of Example 3 (4.14%). This is because MXene (Ti3C2T x ) and flame retardant polyols (vanillyl alcohol-based phosphorus-containing diols) improve the thermal stability and flame retardancy of polyurethane foam materials.
[0052] The saturated adsorption capacity of the polyurethane foam prepared in Example 6 was analyzed. The results are as follows: Figure 5 As shown in the figure, the adsorption experiments were carried out on different organic solvents and oils, among which the adsorption capacity of chloroform was 36.97 g·g -1 , for soybean oil it can reach 9.40g·g-1 , for crude oil it can reach 4.92g·g -1 , indicating that the polyurethane foam has oil adsorption capacity. Combined with the contact angle, it further indicates that the prepared composite foam has oil-water selective adsorption and separation performance and can adsorb crude oil. The schematic diagram of the crude oil adsorption process with and without light conditions is shown in Figure 6 shown.
[0053] The light-to-heat conversion performance of the polyurethane foams prepared in Example 3 and Example 6 was analyzed. The results are as follows: Figure 7 As shown, under simulated lighting conditions, the composite foam can perform efficient photothermal conversion and can be heated to 95.3°C within 360s, which is 67.4°C higher than that of Example 3 (27.9°C).
[0054] The present invention uses castor oil, a widely available and renewable biomass, as the main raw material to prepare polyurethane foam, which is green and environmentally friendly; Ti3C2T x Compared with unmodified foam, the polyurethane soft foam cured with PDMS has excellent mechanical properties and super hydrophobicity, and can perform continuous oil-water separation; the prepared composite polyurethane foam has excellent photothermal conversion performance; at the same time, the composite foam has good flame retardant properties, and the limiting oxygen index can reach 27.3% when the performance is optimal. The multifunctional integration of castor oil-based polyurethane foam broadens the scope of application of polyurethane foam.
Claims
1. A method for preparing a bio-based flame-retardant polyurethane soft foam with photothermal conversion performance, characterized in that: The method comprises the following steps: (1) dissolving vanillyl alcohol in a NaOH aqueous solution to obtain a brown-yellow sodium phenolate aqueous solution, dissolving phenylphosphoryl dichloride in ethyl acetate, and adding the solution dropwise to the sodium phenolate aqueous solution under an ice bath condition, wherein the molar ratio of vanillyl alcohol to phenylphosphoryl dichloride is 1.8-2.5:1, obtaining an upper pale yellow liquid, washing with a NaOH aqueous solution and hot water respectively, and rotary evaporating to obtain a yellow viscous liquid, i.e., a flame retardant polyol; (2) mixing 40-80 parts of castor oil, 0-20 parts of flame retardant polyol, 20 parts of polytetrahydrofuran, 5-10 parts of MXene powder, 2.0-3.6 parts of a foaming agent, 1.0-2.0 parts of a catalyst, and 1.2-2.4 parts of a foam stabilizer uniformly by weight to prepare component A; adding 55-65 parts of isocyanate of component B to component A, foaming and aging to obtain a loaded Ti3C2T x Polyurethane soft foam; (3) Loading Ti3C2T x The polyurethane soft foam was immersed in 1wt.%~5wt.% PDMS n-hexane solution and ultrasonically treated, and then dried and solidified to obtain a bio-based flame retardant polyurethane soft foam with photothermal conversion performance.
2. The method for preparing the bio-based flame-retardant polyurethane soft foam with light-to-heat conversion performance according to claim 1, characterized in that: In step (1), the molar ratio of vanillyl alcohol to phenylphosphoryl dichloride is 2.2:1, and the concentration of the NaOH aqueous solution is 2.2 mol·L -1 .
3. The method for preparing the bio-based flame-retardant polyurethane soft foam with light-to-heat conversion performance according to claim 1, characterized in that: The hydroxyl value of the flame retardant polyol in step (1) is 60 to 65 mg KOH g -1 .
4. The method for preparing the bio-based flame-retardant polyurethane soft foam with light-to-heat conversion performance according to claim 1, characterized in that: The weight proportions of the components in step (2) are as follows: 40-80 parts of castor oil, 20 parts of flame retardant polyol, 20 parts of polytetrahydrofuran, 8 parts of MXene powder, 3.0 parts of foaming agent, 1.3 parts of catalyst, 1.8 parts of foam stabilizer, and 55-65 parts of isocyanate.
5. The method for preparing the bio-based flame-retardant polyurethane soft foam with light-to-heat conversion performance according to claim 1, characterized in that: In step (2), the catalyst is at least one of triethylenediamine, N-methylmorpholine, N-ethylmorpholine and stannous octoate; the foam stabilizer is one of Maitu L580 and Maitu L-3881; and the isocyanate is any one of toluene diisocyanate, diphenylmethane diisocyanate, polyphenylmethane polyisocyanate and isophorone diisocyanate.
6. The method for preparing the bio-based flame-retardant polyurethane soft foam with light-to-heat conversion performance according to claim 1, characterized in that: The MXene powder in step (2) is a single layer Ti3C2T x powder.
7. The method for preparing the bio-based flame-retardant polyurethane soft foam with light-to-heat conversion performance according to claim 1, characterized in that: In step (2), castor oil, polytetrahydrofuran, and MXene powder were first stirred and ultrasonically dispersed for 1-2 h to fully mix, and then mixed with flame retardant polyol, foaming agent, catalyst, and foam stabilizer at 600 r·min. -1 Stir for 3 to 6 minutes to mix well.
8. The method for preparing the bio-based flame-retardant polyurethane soft foam with light-to-heat conversion performance according to claim 1, characterized in that: The temperature in the aging step in step (2) is 50-100°C and the time is 10-36 h; the ultrasonic treatment time in step (3) is 0-2 h, the curing temperature is 60-100°C and the curing time is 10-24 h.
9. A bio-based flame-retardant polyurethane soft foam with photothermal conversion performance obtained according to the method of any one of claims 1 to 8.
10. Use of the bio-based flame-retardant polyurethane soft foam according to claim 9 in oil-water separation and flame retardancy.
Citation Information
Patent Citations
Preparation method of photo-thermal super-hydrophobic polyurethane sponge for oil-water separation
CN118005992A
Bio-based phosphorus flame retardant, epoxy resin and preparation method thereof
CN118684705A
Multifunctional vegetable oil-based polyurethane soft foam as well as preparation method and application thereof
CN118725239A